(3eHGOF GdeMGSHI GdeGdjI habG deYGjjQ GdeMGSHI GdOhdjI habG deYGjjQ GdeMGSHI GdeUQjI hGdOhdjI (B:s (3GdeMGSHI Yf GdfbOjI(B- (3GdYedGA(B- (3ChQGb GdbHV(B- (3GdeNRhf(B- (3GdCUhd WhjdI GdCLd(B- (3GdCNWGA GdeMGSHjI hcjajI eYGdLJgG (B/s - (3TMGJI, GdSjO TMGJIs; (3SdjeGf, eYJR MSjf hBNQhfs ((3GdEScfOQjI(B: s (3OGQ GdJYdje GdLGeYj(B, s)
(3JfGhd gPG GdcJGH eHGOF GdeMGSHI GdeGdjI habG deYGjjQ GdeMGSHI GdOhdjI habG deYGjjQ GdeMGSHI GdeUQjI hGdOhdjI, MjK JMOK ef NdGd aUhdg Yf GdeMGSHI Yf GdfbOjI hGdYedGA hChQGb GdbHV hGdeNRhf HGdGVGaI Gdi GdCUhd WhjdI GdCLd hGdCNWGA GdeMGSHjI hcjajI eYGdLJgG(B. s
Keywords: (3GdeMGSHI GdeGdjIs; (3eYGjjQ GdeMGSHIs